332 GEMS: Geriatric Emergency Service - Outputs and Outcomes from the Acute Floor Team. (16th September 2019) - Cornally, Lorna; Hayes Brennan, Megan; Reddy, Danielle; Gallagher, Grainne; O'Callaghan, Maureen; Mulholland, Ann; Gibbons, Ruth; Nolan, Jane; Normoyle, Cathriona; Ahern, Emer
Abstract: Background: Frailty is now a key concept in healthcare planning and delivery and is driving vertical and horizontal integration. The positive narrative of Frailty is further emphasised by the growing scientific evidence in the prevention, reversal and modification of Frailty. Early identification of Frailty and early intervention with Comprehensive Geriatric Assessment (CGA) is fundamental. Older people with Frailty admitted to hospital who receive a CGA early are more likely to return home. Benefits are seen early and are sustained (Ellis et al 2011). Methods: The aim of GEMS is to improve care, outcomes and the patient experience for older people living with Frailty. All people aged 75 years and older who attend as an emergency are screened on triage using the Variable Indicative of Placement Tool (VIP). Screening is automatic and mandatory. The GEMS Acute Floor Team respond early to those who screen positive by starting a CGA. The GEMS Home Team case manage those who are admitted. Results: Over 2 years 10, 037 patients were triaged. The median time from arrival to VIP was 15 minutes. 43% screened positive for Frailty. 66% received a CGA. The median time from VIP to CGA was 1.7 hours. 84% identified at risk of polypharmacy, 27% at risk of malnutrition, 29% with delirium. 74% were admitted from home. 78% returned to pre-admission residence. 4% new admissions to NH care. Median length of stay was 7 days. The readmission rate within 30 days was 16%. 7% in hospital mortality. Conclusion: The GEMS Team have developed and delivered a pioneering integrated care approach to the management of older person at high risk of adverse outcomes attending the acute floor.